Perceptions of a Continuing Professional Development Portfolio Model to Enhance the Scholarship of Teaching and Learning. (April 2014) - Tofade, Toyin; Abate, Marie; Fu, Yunting
Objective: To obtain feedback about the potential usefulness of a continuing professional development (CPD) portfolio for enhancing a faculty or practitioner's scholarship of teaching and learning (SoTL). Method: A CPD portfolio approach to the SoTL was distributed in advance to registrants of the 2011 Annual AACP Teacher's Seminar. In an interactive workshop, faculty facilitators described a model for a CPD process applied to the development of an individual's SoTL. During the workshop, participants were asked to complete the initial sections of the portfolio to develop a personal plan for success in the SoTL. Post workshop, an evaluation form was distributed to the participants to obtain feedback about the CPD approach. Completed evaluation forms were collected, collated, and summarized. Results: A total of 53 (14.1%) workshop participants completed the evaluation form of the 375 attendees. In all, 25 assistant professors, 14 associate professors, 4 full professors, 10 residents/students, 22 clinical, and 2 research faculty submitted evaluations. The proposed uses for the portfolio model selected most often by the responders were for personal development, faculty evaluation, increasing the SoTL, new faculty development, preceptor development, and residency training. Implications: A structured CPD portfolio model might be useful for the professional development of the SoTL.